Advanced Materials for Electrochemical Energy Conversion and Storage Devices - Santos, Diogo Miguel Franco dos; Šljukić, Biljana (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The book "Advanced Materials for Electrochemical Energy Conversion and Storage Devices" reports new, improved electrocatalytic materials for batteries, capacitors, and fuel cells. These advances are expected to significantly impact the performance of electrochemical energy conversion and storage devices and, consequently, their commercialisation. This book is intended to be a valuable tool for those from industry and academia interested in knowing more about the field.